Stop smoking clinics in Malaysia: characteristics of attendees and predictors of success - Wee, L.H.; Shahab, L.; Bulgiba, A.; West, R. (2011)
Introduction: As Stop Smoking Clinics (SSCs) become more common across the globe, it is important to know how far one can make broad generalisations concerning characteristics of smokers who attend these clinics and factors that predict their success. This involves accumulation of data from different countries. Objective: The aim of this study was to identify characteristics of smokers and factors leading up to quitting with clinics in Malaysia. Method: Records from 629 smokers who had sought help from five selected SSCs in Malaysia from January 2006 to June 2007 were analysed. Results: The characteristics of smokers attending Malaysian smoking clinics were broadly similar to those in Western countries. Consistent with the findings from other countries, older age and longest duration of previous quit attempts were associated with successful smoking cessation. Greater baseline carbon-monoxide readings (OR 0.96, 95 CI 0.93-0.99: p = 0.013). but not Fagerstrom Test for Nicotine Dependence (FTND), predicted failure to quit at six-month in multivariate analysis. Success rates varied greatly between clinics even after adjusting for all other predictors. Conclusion: In these rare data from a non-Western culture some predictors of successful smoking cessation appeared to generalise from Western smokers but the universal validity of the FTND in particular needs to be examined further. (C) 2010 Elsevier Ltd. All rights reserved.